Host Cell Proteins: The Hidden Side of Biosimilarity Assessment. Issue 12 (14th September 2015) - Mihara, Kazutoshi; Ito, Yae; Hatano, Yukichi; Komurasaki, Yoshikazu; Sugimura, Atsushi; Jones, Marisa; Liu, Haiyan; Mai, Shing; Lara‐Velasco, Oscar; Bai, Lin; Ketkar, Amol; Adams, Michael; et al.
Abstract : One major concern with biosimilars is that small differences compared with reference products might lead to unforeseen immunogenicity, thus affecting patient safety and drug efficacy. Differences could be due to either post‐translational modifications of the therapeutic protein and/or to traces of impurities from the manufacturing process. The results presented in this communication illustrate the efforts to assess "biosimilarity" of a biosimilar candidate to a reference product for a specific group of process‐related impurities, the host cell proteins (HCP). Extensive characterization of HCP in the drug substance of a biosimilar candidate revealed the identity of HCP copurifying with the protein of interest and guided process development to improve overall HCP clearance in the downstream process. The data presented illustrate the challenge of matching the reference product on either quantitative or qualitative aspects of HCP impurities. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:3991–3996, 2015